Pengaruh strategi oprasional The Influence of Operational Strategy, Human Resource Management, and Technology Utilization on the Efficient Performance of Mochi Food MSMEs at MMTC Raya Market - Aprinawati; Paula Florensia Munthe; Adelina Lubis; Etri br Kaban (LPPM STIE EKA PRASETYA, 2025)
The purpose of this study is to examine how technology use, humanresource management (HRM), and operational strategies affect the operationalefficiency performance of MSMEs in the food industry in Pasar Raya MMTC.Questionnaires were given to MSME operators at the Mochi Jinels store in PasarRaya MMTC in order to gather data using a quantitative approach. To investigatethe combined effects of these three parameters on operational efficiency,multiple linear regression analysis was used. While HRM management does notsignificantly affect MSME food industry efficiency, the results demonstrate thatoperational strategies and technology utilization do. Although HRM issuescontinue to be a barrier, it is anticipated that the combination of suitable tacticsand efficient technology use will improve operational efficiency. In order to boostcompany growth and sustainability in the traditional food industry, MSMEoperators and policymakers can benefit greatly from these findings as theyformulate more effective development strategies.